Novel Insights Into the Multifaceted Functions of RNA n6-Methyladenosine Modification in Degenerative Musculoskeletal Diseases - Li, Hengzhen; Xiao, WenFeng; He, Yuqiong; Wen, Zeqin; Cheng, Siyuan; Zhang, Yi; Li, Yusheng (Frontiers in Cell and Developmental Biology, 2021)
N6-methyladenosine (m6A) is an important modification of eukaryotic mRNA. Since the first discovery of the corresponding demethylase and the subsequent identification of m6A as a dynamic modification, the function and mechanism of m6A in mammalian gene regulation have been extensively investigated. ‘Writer’, ‘eraser’ and ‘reader’ proteins are key proteins involved in the dynamic regulation of m6A modifications, through the anchoring, removal, and interpretation of m6A modifications, respectively. Remarkably, such dynamic modifications can regulate the progression of many diseases by affecting RNA splicing, translation, export and degradation. Emerging evidence has identified the relationship between m6A modifications and degenerative musculoskeletal diseases, such as osteoarthritis, osteoporosis, sarcopenia and degenerative spinal disorders. Here, we have comprehensively summarized the evidence of the pathogenesis of m6A modifications in degenerative musculoskeletal diseases. Moreover, the potential molecular mechanisms, regulatory functions and clinical implications of m6A modifications are thoroughly discussed. Our review may provide potential prospects for addressing key issues in further studies.